Differences in Commitment Enhancement to the Organization Between Generation X and Generation Y (Analysis of Empowerment and Values) - Adiawaty, Susi; Moeins, Anoesyirwan; Sunaryo, Widodo (Journal of World Science, 2024)
This research aims to determine and analyze differences in increasing commitment to the organization between Generation X and Generation Y. The method used in this research is descriptive with a qualitative approach. The research results found a significant difference in the level of commitment to the organization between Generation X and Generation Y. This difference can be attributed to differences in perceptions of empowerment and organizational values. Generation Y tends to show higher levels of commitment commitment because they are more open to participation in decision-making and value flexibility, innovation, and opportunities for development. They accept and are encouraged by empowering practices within the organization and values that align with their personal and professional aspirations. On the other hand, Generation X, although recognizing the importance of empowerment and organizational values, may need to be more skeptical or have lower expectations, which affects their level of commitment to the organization. This research has implications for Generation Y; organizations can focus on implementing broader empowerment practices, providing space for participation in decision-making, and providing opportunities for innovation and professional development. Meanwhile, for Generation X, efforts can be focused on clarifying organizational values and providing a more personalized approach to supporting their career development. Additionally, organizations can also consider customized training and development programs to suit the needs and preferences of different generations. Thus, this research provides valuable insights for human resource management in responding to generational differences in the workplace to increase the level of commitment and overall organizational performance.